The Effects of Free Childcare on Labor Supply and Children - Anna Busse; Christina Gathmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Many governments have introduced generous childcare subsidies to allow all children access to early childhood education. The effects of these costly programs are however still debated. In this paper, we use the introduction of free public childcare in several states in Germany to analyze its effects on children and their families. Our results suggest that the effects of public childcare depend on the child's age: free public childcare for 3-year-olds increases attendance and female labor supply, while it reduces childcare attendance for 5-and 6-year-olds. After the policy reforms, 3-year-olds improve their developmental skills in the short-run while there might be some detrimental effects for older preschool children.
Keywords: J13; J22; J18; 330